FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PEMBELIAN ANTIBIOTIK - Uswatun Khasanah; Witri Pratiwi; Tiar M Pratamawati; Tridaya P Handayani; Mateus Sakundarno Adi (MEDIA ILMU KESEHATAN, 2020)
Background: Antibiotics are a group of drugs used to treat infectious diseases. Consumption of antibiotics must be adhere to the indications and dosages, so they must be prescribed by a doctor. However, in daily practice antibiotics can be purchased freely by the public without using prescription. Objective: This study aims to analyse the factors associated with purchasing antibiotics without prescription in the city of Cirebon. Method: This study was an observational study with a cross-sectional approach. Primary data was collected through a validated questionnaire against people who bought antibiotics without prescription at five pharmacies in the city of Cirebon. Samples recruited using consecutive sampling method with a total of 299 respondents. The Spearman rank test was used to analyse the data. Results: 246 out of 299 (82.3%) respondents purchased antibiotics without prescription. Results showed that level of education (r=0.267, p=0.001), socioeconomic status (r=0.217, p=0.001), and profession (r=0.132, p=0.022) are significant, while sex (r=0.068, p=0.239) and distance to facility (r=0.102, p=0.054) are not. Conclusion: Level of education, socioeconomic status, and profession are significantly related to purchase of antibiotics without prescription in the city of Cirebon.